Papa Andina - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Papa Andina is a network that coordinated actions with a broad network of public and private partners in Bolivia, Ecuador and Peru. One of its main objectives was to promote innovation systems for poor farmers to improve their food security, facilitate market access and reduce poverty. It develops, uses and promotes participatory methodologies in fostering pro-poor innovation in market chains in order to improve food security and market access for small farmers. In the process, it links research and development organizations, the business sector, the national public authorities and local farmers, to generate collective action to respond to the needs of smallholders.